UPAYA PENCEGAHAN KENAKALAN REMAJA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH ATAS - Istiqomah Nur Ahya; Sri Mariana; Miftahul Fitri; Hila Liani; Oktami Achni; Tri Asthi Wulandari; Devi Saputri; Doni Aprizal Hadi; Wulan Musana Putri; Arya Tri Agustin K (STKIP Persada Khatulistiwa Sintang, 2025)
ABSTRACTJuvenile delinquency is a social issue that requires serious attention from various parties, particularly families, schools, and the community. This community service activity aims to provide education and guidance to high school students to prevent deviant behavior and improve the overall quality of education. The implementation methods included lectures socialization and student development activities emphasizing moral and religious values. The program targeted high school students who are vulnerable to negative influences such as unhealthy peer interactions, excessive use of social media and aggressive behavior. The results of the activity indicate an increase in students understanding of the impacts of juvenile delinquency and an improvement in their attitudes discipline, and learning motivation. The posttest scores showed a significant increase compared to the pretest results demonstrating the effectiveness of the interventions provided. This program is expected to serve as a sustainable preventive effort to develop well-behaved, disciplined, and high-quality young generations.Keywords: juvenile delinquency, prevention, educational quality ABSTRAKKenakalan remaja merupakan salah satu permasalahan sosial yang perlu mendapatkan perhatian serius dari berbagai pihak, terutama keluarga, sekolah, dan masyarakat. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memberikan edukasi dan pembinaan kepada remaja di Sekolah Menengah Atas agar mampu menghindari perilaku menyimpang serta dapat meningkatkan mutu Pendidikan disekolah. Metode pelaksanaan kegiatan dilakukan melalui ceramah, sosialisasi, dan pembinaan yang menekankan pada nilai-nilai moral serta agama. Sasaran kegiatan adalah remaja di Sekolah Menengah Atas yang rentan terhadap pengaruh negatif seperti pergaulan bebas, penyalahgunaan media sosial, dan perilaku agresif. Hasil kegiatan menunjukkan adanya peningkatan pemahaman peserta tentang dampak kenakalan remaja serta meningkatnya nilai siswa dalam menunjang mutu pendidikan. Kegiatan ini diharapkan menjadi langkah preventif yang berkelanjutan dalam menciptakan generasi muda yang berakhlak, disiplin, dan bermutu.Kata kunci : kenakalan remaja, pencegahan, mutu pendidikanJuvenile delinquency is a social issue that requires serious attention from various parties, particularly families, schools, and the community. This community service activity aims to provide education and guidance to high school students to prevent deviant behavior and improve the overall quality of education. The implementation methods include